Anomalous origin of coronary arteries with an interarterial course: pictorial essay - Ferreira,Ana Flávia Pina (2019)
Abstract Coronary arteries originating from the contralateral (noncoronary) sinus and having an interarterial course, in which they run from the ascending aorta to the pulmonary trunk, is a potentially fatal anomaly. Computed tomography (CT) angiography facilitates the recognition and therapeutic planning of such anomalies because of its ability to acquire high-resolution images of the entire course of the coronary artery, as well as of the accompanying atherosclerotic involvement. The right coronary artery originating from the left coronary sinus is the most prevalent anomaly of this type and usually implies a better prognosis, the interarterial course being classified as "high" or "low", depending on whether it is above or below the level of the pulmonary valve, with consequent stratification of the risk and the treatment. However, it is known that there is a high risk of sudden death among patients with a left coronary artery of anomalous origin from the right sinus. In such cases, surgical treatment is recommended, regardless of whether there are symptoms or evidence of ischemia. Given the importance of those aspects, which can be identified on CT of the chest or CT angiography of the aorta, this pictorial essay aims to illustrate such anomalies to facilitate their recognition and description by radiologists who are not specialists in cardiac imaging.